A review on synthesis of magnetite nanoparticles and their applications in cancer therapy - Sukma, Mairi; Dari, Ulan; D, Rahmad Agustyan; Silvini, Yaumil; Putri, Rahayu; Arivatussaqdiyah, Arivatussaqdiyah; Akram, Habibul (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this literature review is to understand how to synthesize magnetite nanoparticle materials Fe₃O₄ using the coprecipitation method and to explore the utilization of magnetite nanoparticles as anti-cancer drugs. The data and/or information collected comes from both primary and secondary sources. Information regarding magnetite nanoparticles is limited to the last eight years, while information on cancer and human health is limited to the last ten years. In this study, the coprecipitation method used was surface adsorption at a molar ratio of 1:3 with the preparation of a 0.1 M solution consisting of ferrous (FeCl3.6H2O) and ferric (FeCl2.4H2O) ions with mechanical agitation at around 2000 rpm, heated at a temperature of 70°C, and stirring conditions increased up to 7500 rpm. The design of the anti-cancer drug preparation has bioavailability and biocompatibility within the human body. From the results of this literature review, it can be concluded that the synthesis of magnetite nanoparticles using the coprecipitation method can control the structural form and size of magnetite nanoparticles, and the drug will selectively attack cancer cells based on its cytotoxic properties.